Model Shariah Relationship Marketing dalam Meningkatkan Kepuasan dan Loyalitas pada Lembaga Keuangan Mikro Syariah - Anita Rahmawaty (Faculty of Sharia and Law - Sunan Kalijaga State Islamic University, 2015)
This research aims to test the theoretical model of the effect of shariah relationship marketing, customer value and product advantage on satisfaction and loyalty. This research is different from previous researches by developing a new variable, namely the shariah relationship marketing predicted to influence satisfaction and loyalty. This research is a survey research by using a quantitative approach. The research data are obtained from 185 respondents by using convenience sampling technique. The research model testing technique uses the path analysis approach. The results showed that shariah relationship marketing positively and significantly effects on customer value, product advantage, satisfaction and loyalty. Nevertheless, in this research, it is found also that product advantage is not related to satisfaction and loyalty. Thus, the research findings suggest that shariah relationship marketing and customer value are the important variables that affect the satisfaction and loyalty.